Occupational exposure to ultraviolet radiation (UVA / UVB) in agricultural workers in the province of Cartago, Costa Rica - Araya-Solano, Tannia (2021)
Ultraviolet radiation constitutes a source of risk for the agricultural sector. In Costa Rica, no data have been published on the exposure to this physical agent, for this reason an exploratory research has been developed whose objective was to quantify the level of ultraviolet radiation to which the collaborators of the agricultural areas (north zone and El Guarco, in Cartago) are exposed, as well as to estimate the standard erythema doce. The radiation level was measured from 6:00 until approximately 15:00 hour. The data were analyzed using statistical methods, and farm workers were surveyed to determine the skin phenotype, most exposed areas of the skin, and other information. The main results showed that the minimum irradiance reported was 1,9 W/cm2, and the maximum was 160,9 W/cm2; the highest average levels were reported between 10:00 and 13:00 hours. The time of the year with the highest level of irradiance was the dry season, in the north zone, with 167 W/cm2 as maximum. The standard erythema dose was estimated between 2,3 and 9,8, exceeding that recommended by the International Commission on Illumination. The ultraviolet index was found between 8 and 12, classified as high and very high. Under the conditions described, the risk of erythema for the collaborators in the farms was increased. A matrix is proposed to determine risk by exposure, taking into account aspects such as task or position, altitude, time of year, level of irradiance, part of the body exposed, and skin phenotype.